Partisipasi Masyarakat di Sekitar Sekolah Dalam Pembentukan Karakter Gotong Royong Siswa di SDNegeri 01 Kandis - Wahyu Adi Pratama; Magdad Hatim; Nyiayu Fahrizah Fuadiah (Journal on Education, 2024)
In improving children's character, it is not only focused on government but also the needs of society. Society is one of the most important parts in the process of forming children's character, especially in the school environment. In this way, the researcher analyzes community participation in improving the mutual cooperation character of class I students. The formulation of the problem in this research is "How is the mutual cooperation character of students at SD Negeri 01 Kandis formed through community participation?" This research aims to find out how the mutual cooperation character of students at SD Negeri 01 Kandis is formed through community participation. This research uses descriptive qualitative research. The data collection techniques used are observation, interviews and documentation techniques. The results of this research show that students are able to work together on their own initiative, although there are still some students who do not want to work together.